UGT1A and TYMS genetic variants predict toxicity and response of colorectal cancer patients treated with first-line irinotecan and fluorouracil combination therapy - Martinez-Balibrea, E (Nature Publishing Group, 2010)
BACKGROUND: The impact of thymidylate synthase (TYMS) and UDP-glucoronosyltransferase 1A (UGT1A) germline polymorphisms on the outcome of colorectal cancer (CRC) patients treated with irinotecan plus 5-fluorouracil (irinotecan/5FU) is still controversial. Our objective was to define a genetic-based algorithm to select patients to be treated with irinotecan/5FU. METHODS: Genotyping of TYMS (5′TRP and 3′UTR), UGT1A1(*)28, UGT1A9(*)22 and UGT1A7(*)3 was performed in 149 metastatic CRC patients treated with irinotecan/5FU as first-line chemotherapy enrolled in a randomised phase 3 study. Their association with response, toxicity and survival was investigated by univariate and multivariate statistical analysis. RESULTS: TYMS 3TRP/3TRP genotype was the only independent predictor of tumour response (OR=5.87, 95% confidence interval (CI)=1.68–20.45; P=0.005). UGT1A1(*)28/(*)28 was predictive for haematologic toxicity (OR=6.27, 95% CI=1.09–36.12; P=0.04), specifically for neutropenia alone (OR=6.40, 95% CI=1.11–37.03; P=0.038) or together with diarrhoea (OR=18.87, 95% CI=2.14–166.67; P=0.008). UGT1A9(*)1/(*)1 was associated with non-haematologic toxicity (OR=2.70, 95% CI=1.07–6.82; P=0.035). Haplotype VII (all non-favourable alleles) was associated with non-haematologic toxicity (OR=2.11, 95% CI=1.12–3.98; P=0.02). CONCLUSION: TYMS and UGT1A polymorphisms influence on tumour response and toxicities derived from irinotecan/5FU treatment in CRC patients. A genetic-based algorithm to optimise treatment individualisation is proposed.